Transcendent Flourishing and Auditors’ Behavioral Inertia: Based on the Philosophy of Supra-Self Flourishing through Structural Equation Modeling - Nazarpour, Ali Akbar; Moghadam, Abdolkarim; Rekabdar , Ghasem (Management Strategies and Engineering Sciences, 2027)
The auditing profession constitutes a highly complex and turbulent environment due to the responsibilities imposed upon auditors. In addition to enduring the pressures inherent in this profession, auditors must possess psychological, behavioral, and performance-related capabilities to resist external influence and intermediary interventions in order to preserve their independence. One of the concepts that, from a theoretical perspective, can multidimensionally contribute to strengthening independence within the auditing profession is inertia capability, which, as a construct opposed to organizational behavior tendencies, may enhance the capacity-building process associated with auditors’ independence. The purpose of this study was to examine the effect of transcendent flourishing on auditors’ behavioral inertia based on the philosophical theory of supra-self flourishing. The research instrument was a questionnaire, and Partial Least Squares (PLS) analysis was employed to analyze the collected data. The target population consisted of auditors affiliated with the Audit Organization and private-sector audit firms, who were selected through random sampling and examined over a six-month period. Based on the obtained findings, transcendent flourishing was found to have a positive and significant effect on auditors’ behavioral inertia. In essence, the findings of this study indicate that the presence of positive expectations within society and the professional environment generates greater dynamism in the effective independence-oriented functions of auditors, as motivational drivers can strengthen auditors’ professional philosophy throughout their career paths and enable them to make professional judgments and express opinions independently of any external influence or potential dependency.